Experimental implementation of direct-proportional length-based DNA computing for elevator scheduling problem - Muhammad, Mohd. Saufee; Ibrahim, Zuwairie; Ueda, Satomi; Ono, Osamu; Khalid, Marzuki (2005)
Previously, ideas and implementation methods for solving elevator scheduling problem using DNA computing method had been proposed. In this paper, results of biochemical experiments that have been carried out to realize the computing approach are presented. Every possible elevators travel path combinations are encoded by DNA sequences of length directly proportional to the elevator’s traveling time based on certain initial conditions such as elevators present and destination floors, and hall calls from a floor. Parallel overlap assembly is employed for an efficient initial pool generation of all possible travel path combinations and polymerase chain reaction for sequence amplification. Finally, gel electrophoresis is performed to separate the DNA sequence according to its length, and the shortest DNA sequence representing the elevator’s optimal path can thus be visualized from the gel electrophoresis image. The experimental result shows that the DNA computing approach can be wellsuited for solving such real-world problem of this type of nature.